Optimization of cotton fabrics dyeing process using various natural dye extracts - Rahayuningsih, Edia; Marfitania, Taranipa; Pamungkas, Mukmin Sapto; Fatimah, Wachid Siti (Jurnal Rekayasa Proses, 2022)
Efforts to substitute synthetic dyes on fabrics for natural dyes are currently increasing. Research and innovation are extremely needed to support those attempts so that the quality of natural dyes is more competitive than synthetic dyes. This study aims to optimize the dyeing parameters of cotton fabrics using natural dye extracts derived from the barks of Tegeran (Cudrania javanensis), Merbau (Intsia bijuga), Tingi (Ceriops tagal), and Jambal (Peltophorum pterocarpum), as well as Jolawe (Terminalia bellirica) fruit peel. Varied dyeing parameters included dye concentration, dyeing time and temperature, and material to liquor ratio (MLR). The fixative solutions used were alum, lime, and iron (II) sulfate. The optimized parameters were based on the values of color depth and evenness, measured colorimetrically. Furthermore, the obtained results of the dyeing process under optimized conditions were analyzed for color quality by measuring color coordinates as well as the values of color strength (K/S), washing fastness, and light fastness. The results showed that the optimal dyeing conditions for all natural dye extracts used were the code A extract concentrations (0.0113 g/mL of Tegeran; 0.0115 g/mL of Merbau; 0.0204 g/mL of Jambal; and 0.0582 g/mL of Jolawe), dyeing at 28°C, dyeing time of 30 minutes, and the MLR of 1:30. The resulting color variations were brown, gray, and golden yellow for the Tegeran extract with alum fixative. The highest K/S value was 5.56 for the fabric dyed in Tegeran extract with iron (II) sulfate fixative solution. The washing fastness values for Merbau, Tingi, Jambal, and Jolawe were 3-4 (fairly good) to 4-5 (excellent). Meanwhile, the light fastness values for all dyes were between 4 (good) and 5 (excellent). Overall, the standard procedure for cotton fabric dyeing that meets the minimum standards for textile products is obtained.